The Semiotics of Sustainability in African Contexts: Decolonizing Global Discourses of Development and Prosperity - Adesanmi, T. O.; Adesuyi, O. P.; Awoyele, R. D. (International Journal of Independent Research Studies, 2025)
This chapter explores how the language and imagery of sustainability are constructed and interpreted within African communicative traditions. Using a bipartite theoretical framework involving social semiotics and decolonial discourse theory, it examines how indigenous symbols, proverbs, and visual arts articulate values of balance, cooperation, and environmental care, principles that intrinsically align with the spirit of the United Nations Sustainable Development Goals (SDGs). The discussion contrasts these local semiotic systems with the standardized global icons and slogans of the SDGs, exposing inherent tensions between the demand for universal visual design and the necessity of cultural specificity. The chapter argues that African societies possess enduring semiotic grammars of prosperity and ecological harmony that have been historically overshadowed by Western models of development communication. By foregrounding these indigenous expressive forms, it calls for a decolonized semiotics of sustainability that acknowledges African epistemologies as vital to global prosperity. Ultimately, it proposes that the fusion of African symbolic systems with global SDG imagery can create more inclusive and culturally grounded narratives of sustainable futures. Therefore, sustainability emerges not merely as an environmental or economic imperative, but as a linguistic, cultural, and ethical process rooted in how communities make meaning and envision collective well-being.